Exploring Pharmacy Technician Roles in the Implementation of an Appointment-Based Medication Synchronization Program - Chelsea Renfro; Davis Coulter; Lan Ly; Cindy Fisher; Lindsay Cardosi; Mike Wasson; Kenneth C. Hohmeier (MDPI AG, 2020)
The objective of this study was to qualitatively explore the role of pharmacy technicians in the implementation of an appointment-based model (ABM) medication synchronization program. The purposeful sampling of technicians working within six different locations of a supermarket chain pharmacy in Mississippi and Tennessee was carried out, and the technicians were interviewed between January and April 2018. A semi-structured interview guide was developed based on the Consolidated Framework for Implementation Research (CFIR). Questions gathered information around pharmacy technician demographics and CFIR domains (process, inner setting, outer setting and intervention characteristics). Interviews were audiotaped and transcribed. Two members of the research team performed thematic content analysis. Six full-time, certified pharmacy technicians with 8.3 ± 2.7 years of experience were interviewed. Findings suggest that including hands-on experience with program software is needed during training to successfully implement ABM. A barrier to implementation was the time needed to complete ABM tasks as compared to other tasks. Although some barriers exist regarding implementation, technicians believe that overall, this program has positive benefits for patients. Results from this study signify that ABM implementation can be challenging. Better ABM portal integration with the pharmacy patient profile and appropriate workforce budgeting are key to continued success.